2014
DOI: 10.1007/s00127-014-0863-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity patterns and risk of depression in young adulthood: a 20-year cohort study since childhood

Abstract: Findings from both prospective and retrospective analyses indicate a beneficial effect of habitual discretionary physical activity since childhood on risk of depression in young adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 51 publications
3
49
1
2
Order By: Relevance
“…Recent evidence suggests that the elevated risk of cardiovascular disease in people with mood disorders can be accounted for by their higher prevalence of risk behaviours, such as smoking and physical inactivity . Similar findings have been reported for physical activity (McKercher et al 2014) and weight (De Wit et al 2010;Sanderson et al 2011). For example, smoking is associated with an increased risk of developing depression and having depression is associated with an increased likelihood of taking up smoking (Chaiton et al 2009).…”
Section: Introductionsupporting
confidence: 74%
“…Recent evidence suggests that the elevated risk of cardiovascular disease in people with mood disorders can be accounted for by their higher prevalence of risk behaviours, such as smoking and physical inactivity . Similar findings have been reported for physical activity (McKercher et al 2014) and weight (De Wit et al 2010;Sanderson et al 2011). For example, smoking is associated with an increased risk of developing depression and having depression is associated with an increased likelihood of taking up smoking (Chaiton et al 2009).…”
Section: Introductionsupporting
confidence: 74%
“…For instance, exercise during the juvenile period produced persistent increases in brain-derived neurotrophic factor (BDNF) and complementary improvements in memory function when examined in adulthood. 31 Despite these notable findings that the brain can benefit from health-promoting lifestyle factors such as exercise, the positive effects of such adaptive manipulations during sensitive developmental periods are understudied. For instance, rodent studies demonstrate that exercise in early life can reverse the lasting deleterious effects of early-life stress on brain and behavior, including depressive-like behavior (for review, see Harrison and Baune 35 ).…”
Section: Early-life Exercise Microbiota and The Developing Brainmentioning
confidence: 99%
“…as well as butyrate-producing bacteria (Figure 1). It is possible that increases in these bacteria are mechanistically involved in the ability of early-life exercise to promote brain function or emotional wellbeing across the lifespan, 31 or promote persistent increases in lean mass 5 (Figure 2). and butyrate-producing bacteria are multi-tasking microbiota in that they interact with a variety of pathways to produce extensive neural and metabolic benefits.…”
Section: A Microbial Ecosystem Altered By Early-life Exercise Can Potmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that there is an inverse association between physical activity and likelihood of depression, mainly considering higher levels of physical activity (as recommended in physical activity guidelines), but also at lower doses [17,18]. There is evidence suggesting positive effects of exercise on depression in intervention [19,20], cross-sectional [21], population-based [22], and cohort studies [23-25], indicating that participation in exercise could be an important target of mental health treatments. Further to this, exercise has been shown to be effective as a treatment for clinical depression [26] and anxiety in both adults [27] and adolescents [28].…”
Section: Introductionmentioning
confidence: 99%